Investigation on the Effect of Thermal and Mechanical Treatment to the Offshore Corrosion Behavior of 6351 Aluminum Alloy in Red Sea Environments - Yahya Ali Fageehi; Rajasekaran Saminathan (International Journal of Analytical Chemistry)
This study investigates the effect of artificial aging treatment and mechanical attrition treatment on the corrosion behavior of 6351 Al alloy in Red Sea environment. The artificial aging of the alloy is carried out at temperature range 140°C–240°C in steps of 20°C for various time periods after the solution heat treatment at 530°C for 1 hour. Based on the hardness measurements, the aged specimens are categorized into three, namely, underaged, peak aged, and overaged. The as received alloy specimens are subjected to mechanical attrition treatment in a vacuum chamber using steel balls. Vickers hardness test reveals that there is a remarkable improvement in hardness of mechanical attrition treated specimens compared to that of aged specimens. The aged and mechanical attrition treated specimens were subjected to the corrosion test in Red Sea water using the Autolab instrument. The corrosion tests reveal that the peak-aged composite corrodes more in Red Sea water when compared to that of other groups of specimens. XRD measurements and SEM analysis are carried out to study the surface nature of attrition treated specimens. It is observed that the mechanical attrition treated specimens exhibit a nanocrystalline surface and lead to a decrease in corrosion resistance. However, the annealing of the alloy after attrition treatment optimizes the mechanical and corrosion properties of the alloy.